2012
DOI: 10.3382/ps.2012-02156
|View full text |Cite
|
Sign up to set email alerts
|

Footpad dermatitis in Dutch broiler flocks: Prevalence and factors of influence

Abstract: In some European countries, footpad dermatitis (FPD) is measured as an indicator of broiler welfare. Prevalence and seasonal variation of FPD was determined within broiler flocks (fast-growing breeds) in the Netherlands. Samples were taken from 386 Dutch flocks at 8 slaughterhouses during a period of one year. Prevalence of footpad dermatitis was related to background information gathered using a food chain certification scheme to identify possible factors of influence. On average, 35.5% of the broilers had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 20 publications
2
47
2
9
Order By: Relevance
“…Litter moisture content has been found to influence ammonia emissions (Elliott and Collins, 1982;Liu et al, 2007;Miles et al, 2011), odours (Clarkson and Misselbrook, 1991;Murphy et al, 2014), dust (Roumeliotis et al, 2010), and health issues such as foot pad dermatitis (Bilgili et al, 2009;de Jong et al, 2012). Microbial populations flourish when litter has a moisture content greater than 35-40% (mass water/ mass of litter), which can have consequences including increased odour production and greater risks to bird health and food safety (Eriksson De Rezende et al, 2001;Agnew and Leonard, 2003;Wadud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Litter moisture content has been found to influence ammonia emissions (Elliott and Collins, 1982;Liu et al, 2007;Miles et al, 2011), odours (Clarkson and Misselbrook, 1991;Murphy et al, 2014), dust (Roumeliotis et al, 2010), and health issues such as foot pad dermatitis (Bilgili et al, 2009;de Jong et al, 2012). Microbial populations flourish when litter has a moisture content greater than 35-40% (mass water/ mass of litter), which can have consequences including increased odour production and greater risks to bird health and food safety (Eriksson De Rezende et al, 2001;Agnew and Leonard, 2003;Wadud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Yalçin et al [28] reported effects on beak development, observing that these parameters also can affect keratinaceous tissues. Recently, De Jong et al [22] observed an effect of hatcheries on FPD incidence in chickens, reinforcing a hypothesis that factors affecting embryonic development may be very important for FPD etiology.…”
mentioning
confidence: 84%
“…O'Driscoll and Broom [20] also observed that ducks reared using wide-lip bell drinkers tend to have better footpad scores than ducks reared using nipple drinkers. Usually litter characteristics, management, nutrition, and genetics are considered to be the most important factors on FPD onset [5,14,21,22]. Although these factors are common to all individuals, in a flock several degrees of FPD are observed [12,13].…”
mentioning
confidence: 99%
“…Echter, in dat onderzoek was het niet mogelijk meer specifiek te kijken naar eventuele onderliggende factoren die het broederij effect konden verklaren, waardoor het niet duidelijk was of het in dit geval ging om de invloed van broedcondities, of om bijvoorbeeld de invloed van condities op vermeerderingsbedrijven die waren verstrengeld met broederij, zoals bijvoorbeeld de voeding van de moederdieren (de Jong, et al, 2012b). In een vervolgonderzoek werden kuikens afkomstig uit eieren van hetzelfde vermeerderingsbedrijf gebroed bij twee broederijen en vervolgens geplaatst onder gelijke omstandigheden in één stal.…”
Section: Figuur 36 Het Vleeskuikenbedrijfseffect Voor Uniformiteit (unclassified